2015
DOI: 10.1111/jicd.12197
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of adjunctive moxifloxacin in generalized aggressive periodontitis: a subgroup analyses in Aggregatibacter actinomycetemcomitans‐positive/negative patients from a clinical trial

Abstract: Adjunctive MOX trended toward better clinical responses in A. actinomycetemcomitans-positive patients at baseline. These results suggest that A. actinomycetemcomitans at baseline might modify the effect of adjunctive MOX in GAgP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
(94 reference statements)
0
9
0
1
Order By: Relevance
“…No meta‐analysis was possible based on other bacteria or other antibiotics, due to a paucity of data in the five included papers. Therefore, although some papers (Ardila & Guzman, ; Guerrero et al, ) suggested that the adjunctive antibiotics may be more effective in improving clinical outcomes in patients carrying some specific periodontopathogenic bacteria such as A. actinomycetemcomitans , this is not supported by the evidence produced by this review.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…No meta‐analysis was possible based on other bacteria or other antibiotics, due to a paucity of data in the five included papers. Therefore, although some papers (Ardila & Guzman, ; Guerrero et al, ) suggested that the adjunctive antibiotics may be more effective in improving clinical outcomes in patients carrying some specific periodontopathogenic bacteria such as A. actinomycetemcomitans , this is not supported by the evidence produced by this review.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, when no antibiotics were prescribed, the change from ≥5 mm to ≤4 mm PPDs was found to be 52.6% for A. actinomycetemcomitans +ve and 60.9% for A. actinomycetemcomitans −ve individuals. Overall, both Guerrero and co‐workers and Ardila and co‐workers suggested that all patients benefitted from the antibiotic adjunct, although its clinical effect seemed to be more pronounced (but not statistically significant) in A. actinomycetemcomitans +ve patients (Ardila & Guzman, ; Guerrero et al, ). On the contrary, Cionca and co‐workers concluded that the adjunctive clinical benefits attributable to the antibiotic were obtained regardless of the baseline presence or absence of the six studied periodontal pathogens (Cionca et al, ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations